Online Patient Resources for Ankle Instability - Mostafa M. Abousayed MD, MSc; Jason P. Tartaglion MD; Samuel Zonshayn MD; Navdeep Rai MS; Christopher K. Johnson MS; Andrew J. Rosenbaum MD (Foot & Ankle Orthopaedics, 2018)
Background: The Internet has drastically changed how patients access health-related information. There are several ways the public can access online health-related information such as search engines, blogs, support groups, and webinars. A recent study found that 45% of orthopedic patients searched for information online regarding their injury. Also, 78% believed they had better understanding of their condition after visiting these websites; furthermore, 41% felt the Internet supplied them with questions and concerns to discuss with their physicians. The aim of our study is to evaluate the accuracy, quality, and readability of online available information using the search terms “ankle sprain” and “ankle instability.” Methods: Three search engines (Google, Bing, and Yahoo) were used to search for the terms “ankle sprain” and “ankle instability.” The first 25 websites from each search were collected. Each website was assessed for quality, accuracy, and readability by 3 orthopedic residents blinded to the search term used. Websites were also evaluated for commercial bias and whether written by physicians or not. Results: Twenty sites were identified using Google, 14 using Bing, and 3 using Yahoo while the remaining 19 appeared in multiple search engines. Sixty-nine percent of the websites (39/56) were written by physicians whereas only 21% (12/56) were associated with commercial bias. The mean quality and accuracy of the websites written above a seventh-grade level was statistically significantly higher than those at or below a seventh-grade level ( P = .01). The mean accuracy of websites written by physicians was not statistically different from those not written by physicians ( P = .055). Conclusion: The current study highlights the poor quality and accuracy of online information related to ankle sprains, especially those with commercial bias. Furthermore, although websites written by or under supervision of physicians were found to be of superior quality, a majority of sites were found to have an unacceptably high reading level. Level of Evidence: Level IV, case series.